Psychosocial and Clinical Factors That Differentiate and Predict Patients’ Adaptation to Chronic Diseases - Laza R; Al Ghazi L; Lustrea A; Lazureanu VE; Oancea CI; Luput-Andrica IM; Poplicean EI; Ilina R; Cireap N; Bob F; Olariu N; Ionita I; et al. (Patient Preference and Adherence)
Ruxandra Laza,1 Loredana Al Ghazi,2 Anca Lustrea,2 Voichita Elena Lazureanu,1 Cristian Iulian Oancea,3,4 Ioana Melinda Luput-Andrica,5 Emanuel Ionut Poplicean,4,5 Razvan Ilina,6 Natalia Cireap,6 Flaviu Bob,7,8 Nicu Olariu,5,9 Ioana Ionita,10,11 Sandra Lazar,10,11 Liana Dehelean,12 Radu Stefan Romosan,12 Ana-Maria Romosan12 1Department of Infectious Diseases, Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 2Department of Educational Sciences, University Clinic of Therapies and Psycho-Pedagogical Counseling, West University of Timisoara, Timisoara, Romania; 3Department of Pneumology, Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 4Romania Center for Research and Innovation in Precision Medicine of Respiratory Diseases (CRIPMRD), Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 5Doctoral School Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 6Department of Oncological Surgery-Surgical Semiology, Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 7Department of Internal Medicine II—Nephrology, Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 8Center for Molecular Research in Nephrology and Vascular Disease, Victor Babes University of Medicine and Pharmacy, Timisoara, Romania; 9Center of Hemodialysis, Pius Branzeu County Hospital, Timisoara, Romania; 10Department of Hematology, Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 11Multidisciplinary Research Center for Malignant Hematology (CCMHM), Victor Babes University of Medicine and Pharmacy Timisoara, Timisoara, Romania; 12Department of Neurosciences-Psychiatry, Victor Babes University of Medicine and Pharmacy, Timisoara, RomaniaCorrespondence: Loredana Al Ghazi, Department of Educational Sciences, University Clinic of Therapies and Psycho-Pedagogical Counseling, West University of Timisoara, Bd. Vasile Pârvan 4, Timișoara, 300223, Romania, Tel +40752171111, Email loredana.al@e-uvt.ro Anca Lustrea, Department of Educational Sciences, University Clinic of Therapies and Psycho-Pedagogical Counseling, West University of Timisoara, Bd. Vasile Pârvan 4, Timișoara, 300223, Romania, Tel +40741795465, Email anca.lustrea@e-uvt.roPurpose: Adaptation to chronic disease is an important factor for the quality of life of patients and their families. This research aimed to identify the psychosocial and clinical factors that determine significant differences and best predict the patients’ adaptation to chronic diseases. Understanding these factors enables the design of evidence-based preventive interventions that promote early adaptation.Patients and Methods: A quantitative, non-experimental comparative and predictive study design was conducted. Several clinical, demographic, and psychological factors were measured with an online questionnaire. This study was conducted on a convenience sample of 263 patients with chronic diseases: 63 (24%) had chronic kidney disease with dialysis dependency, 49 (18.6%) had solid neoplasms, 61 (23.2%) had hemopathies, 64 (24.3%) had HIV infection, and 26 (9.9%) had tuberculosis.Results: Adaptation to chronic disease varies based on the type of diagnosis, with lower adaptation seen in conditions that significantly impact daily life, involve comorbidities, and require frequent treatments, like chronic kidney disease. The most significant predictor of adaptation to the chronic disease is the female gender. Other predictive factors are medication adherence, social support, and self-efficacy in managing chronic disease. Patients without comorbidities and fewer medications are more prone to illness denial, alongside younger, urban, employed, and higher-educated patients, potentially neglecting treatment. Patients with comorbidities and the older patients require greater emotional support, with psychological counseling and support groups being beneficial.Conclusion: Current data underlines the need for an individualized approach to chronic disease management, which should consider demographic and psychological factors in addition to clinical ones. It is important to design early interventions for the development of adaptation to chronic disease, which could include individual and family counseling and education programs for medication administration, treatment at home, adherence to a healthy lifestyle, and inclusion of the patient and his family in social support groups.Keywords: adaptation to chronic disease, predictive factors, medication adherence, social support, self-efficacy